KELIMPAHAN JENIS MAMALIA MENGGUNAKAN KAMERA JEBAKAN DI RESORT GUNUNG BOTOL TAMAN NASIONAL GUNUNG HALIMUN SALAK - Abdul Haris Mustari; Agus Setiawan; Dones Rinaldi (Media Konservasi, 2015)
Halimun Salak Mount National Park has many ecosystem and habitat types that support rare and endemic species including mammals. This study aimed to reveal the diversity of mammals in the national park using camera trap and direct observation, setting of live trap, mist net, identification of foot print.  A total of 23 mammals’ species (11 species were recorded  using camera trap) in this study. Based on the capture rate, the highest abundance of mammals was muncak deer (Muntiacus munjak) of 31.25% with an encounter rate of 34.37 photos/100 day, while the lowest was malaysian wood rat (Rattus tiomanicus), treeshrew (Tupaia javanica), plantain squirrel (Callosciurus notatus), malay badger (Mydaus javanensis), leopard cat (Prionailurus bengalensis), and banded linsang (Prionodon linsang) each has 3.12%.  Keyword: camera trap, encounter rate, mamals’abundance